ZnS nanoparticles embedded in porous honeycomb-like carbon nanosheets as high performance anode material for lithium ion batteries. Issue 12 (15th August 2018) - Chen, Hezhang; Zhang, Bao; Cao, Yang; Wang, Xu; Yao, Yingying; Yu, Wanjing; Zheng, Junchao; Zhang, Jiafeng; Tong, Hui
Abstract: ZnS nanoparticles coated with honeycomb-like carbon nanosheets (ZnS@HPC) were synthesized via freeze drying and carbonization methods, using NaCl crystals as hard template. The ZnS@HPC composite possessed a novel three-dimensional network structure and high specific surface area of 128.9 m 2 g −1 . In this composite, ZnS nanoparticles with small diameter of 20–40 nm were embedded in carbon nanosheet matrix. Moreover, nitrogen-doped carbon formed successfully during the carbonization process. The porous carbon matrix provided a conductive network and also worked as a buffer to confine ZnS nanoparticle expansion during lithiation and delithiation process. So, the electrochemical performance of ZnS@HPC composite electrode was much better than that of ZnS and ZnS/C electrodes. As a novel anode material, ZnS@HPC composite exhibited the initial cycle discharge and charge capacities of 1359 and 889 mAh g −1 at 100 mA g −1 ; and showed excellent cycle performance, the discharge capacity achieved 408 mAh g −1 after cycling at 1 A g −1 for 200 cycles.